Controlling of Wastewater Disposal of Toufu And Tempe Industry By The Environment Service In Gandasari Village, Katapang District, Bandung Regency - Christianingsih, Endah; Dewi, Allia Thasyania; Miswan, Miswan (MSJ : Majority Science Journal, 2024)
Coinciding in Gandasari Village. The purpose of this research is to find out the Controlling of Tofu and Tempe Industrial Wastewater Disposal by the Environment Agency in Gandasari Village, Katapang District, Bandung Regency, to find out the relationship of this policy oversight with the State Administration Study Program, as well as to find out how it is implemented in the field. The research method used by the author is a descriptive qualitative research method which describes a phenomenon that exists in the field, by conducting observations, interviews, and documentation. This research is aimed at examining problems related to tofu and tempeh industrial waste water in Gandasari Village which still produces air pollution and water pollution that disturbs the comfort of local residents and has the potential to pollute the environment. The results of the study show that the supervision of industrial waste water disposal must meet the standards in the provisions of the Agreement Letter such as the Environmental Management Efforts and Environmental Monitoring Efforts (UKLUPL) which should be made by industrial actors but in practice this procedure cannot be carried out by the agency. environment due to obstacles from industrial business actors who do not make environmental documents and the lack of knowledge of residents regarding industrial waste water management, this results in the environmental service being unable to carry out supervision and even the environmental service itself does not know about the existence of the tofu and tempeh industry in the village Gandasari So there is a need for counseling related to Tofu and Tempe Industrial waste water management for Tofu and Tempe business people and a Wastewater Disposal Installation (WWTP) for Tofu and Tempe Industry in Gandasari Village.